Phosphatidylinositol 3-Kinase/Akt signal pathway resists the apoptosis and inflammation in human extravillous trophoblasts induced by Porphyromonas gingivalis. (December 2018) - Guo, Haiying; Ren, Hongyu; Liang, Shanshan; Ji, Yaoting; Jiang, Han; Zhang, Ping; Du, Minquan
Highlights: We examined the level of apoptosis and inflammation in HTR-8 cells when infected with P. gingivalis in vitro. P-Akt in HTR-8 cells was activated during cultured with P. gingivalis . PI3K/Akt could resist the apoptosis and inflammation in HTR-8 cells induced by P. gingivalis to some extent. Abstract: Epidemiological studies suggested that periodontitis is a risk factor for pregnancy complications including preterm birth. Porphyromonas gingivalis, a vital periodontal pathogen found in amniotic fluid and intact membranes of women who deliver preterm low birth weight infants, is thought to contribute to preterm labor. However, molecular and cellular interactions between P. gingivalis and placental cells are not clear. In this study, we investigated the effect of P. gingivalis on human extravillous trophoblasts and observed that it triggered apoptosis and inflammation and that Akt was activated in this process. In addition, when Akt activation was inhibited, apoptosis and inflammation was significantly increased. Thus, P. gingivalis infection contributes to preterm low birth weight infants by triggering excessive inflammation and increasing apoptosis in trophoblasts and that the Phosphatidylinositol 3-Kinase/Akt signaling pathway is involved in the regulation of Pg-induced apoptosis and inflammation.